Supporting women of childbearing age in the prevention and treatment of overweight and obesity: a scoping review of randomized control trials of behavioral interventions - Melinda J. Hutchesson; Mette de Jonge Mulock Houwer; Hannah M. Brown; Siew Lim; Lisa J. Moran; Lisa Vincze; Megan E. Rollo; Jenna L. Hollis (BMC Women's Health, 2020)
Abstract Background Women of childbearing age are vulnerable to weight gain. This scoping review examines the extent and range of research undertaken to evaluate behavioral interventions to support women of childbearing age to prevent and treat overweight and obesity. Methods Eight electronic databases were searched for randomized controlled trials (RCT) or systematic reviews of RCTs until 31st January 2018. Eligible studies included women of childbearing age (aged 15–44 years), evaluated interventions promoting behavior change related to diet or physical activity to achieve weight gain prevention, weight loss or maintenance and reported weight-related outcomes. Results Ninety studies met the inclusion criteria (87 RCTs, 3 systematic reviews). Included studies were published from 1998 to 2018. The studies primarily focused on preventing excessive gestational weight gain (n = 46 RCTs, n = 2 systematic reviews), preventing postpartum weight retention (n = 18 RCTs) or a combination of the two (n = 14 RCTs, n = 1 systematic review). The RCTs predominantly evaluated interventions that aimed to change both diet and physical activity behaviors (n = 84) and were delivered in-person (n = 85). Conclusions This scoping review identified an increasing volume of research over time undertaken to support women of childbearing age to prevent and treat overweight and obesity. It highlights, however, that little research is being undertaken to support the young adult female population unrelated to pregnancy or preconception.